PEMBENTUKAN KARAKTER DAN EDUKASI HUKUM CEGAH BULLYING PADA PELAJAR SMA NEGERI 1 MERAUKE - Rudini Hasyim Rado; Restu Monika Nia Betaubun; Nurul Widhanita Y. Badilla (Musamus Devotion Journal, 2022)
As bullying behavior increases by the younger generation, especially at the educational level, it seems to confirm the increasingly crisis of character-based education in today's educational climate. This writing is directed not only to instill but also to shape character through legal education to prevent student bullying at SMA Negeri 1 Merauke, Merauke Regency. The method applied is the method of discussion, question and answer, and character building between the presenters and students. The findings of the service concluded that the degradation of the character values of students was directly proportional to the bullying behavior, this condition was exacerbated by the lack of understanding of the community and current high school students regarding the laws and regulations including the Criminal Code, the Child Protection Act, the ITE Law.